"Don't ever change"? Cultural heritage and social development in "timeless" Luang Prabang. Issue 3 (16th March 2020) - Wilcox, Phill
Abstract : Purpose: This paper considers discourses of preservation in a UNESCO World Heritage Site in a context of a country that pursues an ambitious agenda of development. It argues for a lived contradiction between Luang Prabang, marketed as a timeless, beautiful city of heritage and the rest of Laos, a desperately poor country in dire need of urgent development. It argues that this paradox is enacted by locals and visitors in Luang Prabang. Design/methodology/approach: Researched through fifteen months ethnography in and around the heritage zone of central Luang Prabang, data collection included participant observation and around a dozen interviews with local residents (both domestic and international). Findings: This research demonstrates that because the heritage centre of Luang Prabang cannot develop in the same way as the rest of Laos in view of the focus on preservation, its heritage zone will further become an island of idealised past as the country develops fast around it. Research limitations/implications: This raises important questions about agendas of preservation and development, how these intersect and conflict. This is particularly relevant in countries that are subject to fast track development, including from China. Originality/value: The paper is an updated attempt to consider heritage in Luang Prabang, particularly in an emergent context.